RELIGIOUS TOURISM AND COMPENSATION TO ORPHANS TOGETHER WITH YAYASAN KREASI BANGUN SEMESTA CIREBON BRANCH: WISATA RELIGI DAN PEMBERIAN SANTUNAN KEPADA ANAK YATIM BERSAMA YAYASAN KREASI BANGUN SEMESTA CABANG CIREBON - Suwandi Suwandi; Ilwan Syafrinal; Marsani Asfi (Yayasan Education and Social Center, 2021)
The term Idul Yatama (Orphans Day) is just an expression of joy for orphans because many people paid attention and compensation to them at that time. The focus of the service is doing religious tourism in one of the historical places in Cirebon City, which is now a religious tourism object, namely Sunyaragi Cave. This community service activity method uses the lecture, discussion and question and answer method. The result of this community service activity is that orphans are equipped with knowledge about one of the historical places in Cirebon, namely Sunyaragi Cave, and giving donations to orphans.